2017
DOI: 10.1002/2017gl074368
|View full text |Cite
|
Sign up to set email alerts
|

Highly temporally resolved response to seasonal surface melt of the Zachariae and 79N outlet glaciers in northeast Greenland

Abstract: The seasonal response to surface melting of the Northeast Greenland Ice Stream outlets, Zachariae and 79N, is investigated using new highly temporally resolved surface velocity maps for 2016 combined with numerical modeling. The seasonal speedup at 79N of 0.15 km/yr is suggested to be driven by a decrease in effective basal pressure induced by surface melting, whereas for Zachariae its 0.11 km/yr seasonal speedup correlates equally well with the breakup of its large ice mélange. We investigate the influence 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 69 publications
3
43
0
Order By: Relevance
“…Only when results are fully reproducible -meaning all necessary data and code are available (cf. Mankoff and Tulaczyk, 2017;Rezvanbehbahani et al, 2017) -can new works confidently attribute discrepancies relative to old works. Therefore, in addition to providing new discharge estimates, we attempt to examine discrepancies among our estimates and other recent estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Only when results are fully reproducible -meaning all necessary data and code are available (cf. Mankoff and Tulaczyk, 2017;Rezvanbehbahani et al, 2017) -can new works confidently attribute discrepancies relative to old works. Therefore, in addition to providing new discharge estimates, we attempt to examine discrepancies among our estimates and other recent estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Interannual velocity fluctuations and resulting mass loss due to ice discharge via marine-terminating glaciers in Greenland are relatively well characterized (Andersen et al, 2015;Enderlin et al, 2014;Howat et al, 2007;Mouginot et al, 2015;Rignot et al, 2004;Schlegel et al, 2014). Previous studies have also reported seasonal velocity variability for different glacier systems in Greenland and provided evidence of potential driving mechanisms (Bevan et al, 2015;Howat et al, 2008;Kjeldsen et al, 2017;Moon et al, 2012;Moon et al, 2014;Rathmann et al, 2017). Previous studies have also reported seasonal velocity variability for different glacier systems in Greenland and provided evidence of potential driving mechanisms (Bevan et al, 2015;Howat et al, 2008;Kjeldsen et al, 2017;Moon et al, 2012;Moon et al, 2014;Rathmann et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…The break-up of ice shelves that stabilise the outlet glaciers can lead to accelerations in ice velocity and therefore higher rates of sea level rise [29], but different glaciers respond in different ways to changes at the front [86] and careful modelling studies in combination with good observational data are required to understand the important processes [87]. For example, Rathmann et al [21] showed different seasonal accelerations at neighbouring glaciers Zachariae Isstrøm and 79 glacier in response to very similar runoff rates. Part of the differences were explained by different hydrological regimes but there is also a possibility that response to a climate forcing may be delayed by other glaciological processes such as differing bed topographies, geothermal heat flux or past strain histories.…”
Section: Calving Front Location and Ice Sheet Mass Budgetmentioning
confidence: 99%
“…By consolidating, standardising and integrating satellite remote sensing data, high quality datasets are now accessible to scientists, policymakers and other stakeholders. This data has been used to identify significant trends and changes in ice dynamics in Greenland including identifying significant changes in ice velocity at large outlet glaciers [16], assessing the causes of surface elevation change across the ice sheet [17][18][19][20] as well as assessing the importance of different processes controlling seasonal velocity changes on the ice sheet [21]. The availability of this data is invaluable in communicating the effects of climate change on the cryosphere and the likely impacts on sea level rise and human societies.…”
Section: Introductionmentioning
confidence: 99%